A cross-sectional questionnaire study of tinnitus awareness and impact in a population of adult cochlear implant users - Gomersall, Philip A.; Baguley, David; Carlyon, Robert P. (Lippincott, Williams & Wilkins, 2018)
Objectives: The primary aim was to identify the proportion of individuals within the adult cochlear implant population who are aware of tinnitus and those who report a negative impact from this perception, using a bespoke questionnaire designed to limit bias. A secondary aim was to use qualitative analysis of open-text responses to identify themes linked to tinnitus perception in this population. Design: A cross-sectional questionnaire study of a large clinical population who received an implant from Cambridge University Hospitals, United Kingdom. Results: Seventy-five percent of respondents reported tinnitus awareness. When impact scores for six areas of difficulty were ranked, 13% of individuals ranked tinnitus their primary concern and nearly a third ranked tinnitus in the top two positions. Tinnitus impact was not found to reduce with duration since implantation. The most common open-text responses were linked to a general improvement postimplantation and acute tinnitus alleviation specific to times when the device was in use. Conclusions: Tinnitus is a problem for a significant proportion of individuals with a cochlear implant. Clinicians, scientists, and cochlear implant manufacturers should be aware that management of tinnitus may be a greater priority for an implantee than difficulties linked to speech perception. Where a positive effect of implantation was reported, there was greater evidence for masking of tinnitus via the implant rather than reversal of maladaptive plasticity.